Warming up to technology. - Black, Tom (American City & County, 1998)
Street and highway officials are turning to computer software, weather-monitoring equipment, and anti-icing sprays in an effort to control snow and ice. Anti-icing is the application of liquid brine and various mixtures to roadways to prevent the formation of bonded snow and ice. Deicing is an after-the-fact action that consists of the spreading of salt or other substances onto roadways to melt existing snow and ice. Road weather information systems enhance these strategies by collecting information from solenoids, sensors, and weather-monitoring equipment.